2017
DOI: 10.1177/0004867417714335
|View full text |Cite
|
Sign up to set email alerts
|

Aversive eye gaze during a speech in virtual environment in patients with social anxiety disorder

Abstract: The current study confirms that eye gaze behaviour of social anxiety disorder patients is aversive and that their anxiety symptoms are more dependent on the nature of topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Felnhofer et al [12] too reported significantly higher levels of anxiety, co-presence, and immersion in participants with SAD than in healthy controls. Kim et al [13] exposed 79 individuals with SAD and 51 healthy controls to impromptu speeches on self-related topics to a virtual audience and concluded that individuals with SAD demonstrate less eye gaze towards the audience than healthy controls. Lange and Pauli [14] explored avoidance behavior among individuals with high vs. low social anxiety (n = 50).…”
Section: Virtual Social Worldsmentioning
confidence: 99%
“…Felnhofer et al [12] too reported significantly higher levels of anxiety, co-presence, and immersion in participants with SAD than in healthy controls. Kim et al [13] exposed 79 individuals with SAD and 51 healthy controls to impromptu speeches on self-related topics to a virtual audience and concluded that individuals with SAD demonstrate less eye gaze towards the audience than healthy controls. Lange and Pauli [14] explored avoidance behavior among individuals with high vs. low social anxiety (n = 50).…”
Section: Virtual Social Worldsmentioning
confidence: 99%
“…In addition to self‐reported data, past virtual reality experiments have captured physiological data by using EDA, 12‐15 which can be indicative of high levels of arousal or stress, 16 as well as eye gaze behavior such as eye fixations, 17‐19 which can be indicative of not only attention, 18 but anxiety, 17 engagement, 20 as well as social functioning 19 . Virtual reality studies capturing EDA have explored public speaking anxiety, 17 and posttraumatic stress disorder 21 among other interests. Concerning sense of embodiment in virtual reality, studies have previously captured EDA in response to threat to a virtual body part, 9,12 and in order to measure the influence of stress on body ownership 22 .…”
Section: Related Workmentioning
confidence: 99%
“…Automatic data collection also allows subtle aspects of social interactions to be evaluated for signs of interpersonal bias. This has included interpersonal distance (Simões et al., 2020) and eye contact (H. Kim et al., 2018). These implicit measures have been used to better understand patient–provider interactions and interpersonal bias and showcase a key advantage of VR research ( data collection ).…”
Section: Vr As a Research Tool In Health Psychology: Past Present And Futurementioning
confidence: 99%